Peran Profitability sebagai Moderasi: Sales Growth, Transfer Pricing, Capital Intensity dan Tax Avoidance - Maya Novitasari; Srikalimah Srikalimah; Munari Munari (Owner : Riset dan Jurnal Akuntansi, 2025)
Tax is the main income for the government, so it is very reasonable if the government wants all taxpayers in Indonesia to pay their tax obligations according to applicable policies. This study aims to analyze and prove the effect of sales growth, transfer pricing, and capital intensity on tax avoidance with profitability as a moderating variable in real estate and property companies listed on the Indonesia Stock Exchange during the 2020-2023 period. The data sources were obtained from the Indonesia Stock Exchange website and the official websites of each related company. The population in this study was 92 companies with a total sample of 328. This study shows that sales growth has an effect on tax avoidance, transfer pricing has no effect on tax avoidance, and capital intensity has no effect on tax avoidance. In addition, it is also shown that profitability is unable to moderate the effect of sales growth on tax avoidance, profitability is unable to moderate the effect of transfer pricing on tax avoidance, and profitability is unable to moderate the effect of capital intensity on tax avoidance.